A Inclusão da pessoa cega em cursos a distância, mediada por recursos de tecnologia assistiva : uma proposta de design instrucional - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
In today's society, the use of technological resources for the development of various activities has become commonplace. Faced with this reality, the present research focuses on a specific audience and context: blind individuals in distance learning courses. When we conceive that at present, distance education has become a viable alternative for individuals belonging to the most diverse social and cultural classes to have access to education, without the physical space being a barrier capable of limiting or even making this access unfeasible, objective research to analyze the effectiveness of Assistive Technology resources and their contributions to the inclusion of the blind person in the scope of the EAD, as well as to present, by means of a design and instructional proposal, practices that assist in the blind individuals' access to this modality of teaching, in a way optimized. In order to do so, we analyze, during the research, in addition to theoretical constructs related to the theme, experiences that come from the course Introduction to Distance Education: theory and practice, which, through the Center for Teaching and Learning in Network (CEAR) of the State University of Goias (UEG), was offered to 10 blind individuals, being these, older than 18 years and having as minimum level of schooling, the complete high school. At the end of the course, in order to fulfill the proposed objectives, we applied a questionnaire composed of 20 objective questions, using the Likert scale, with a gradation of 1 to 5, 1 being considered poor and 5 being excellent. After collecting and analyzing the data, we present to educational institutions a proposal for instructional design, so that courses of this nature are accessible to all people, regardless of whether they have a disability. The analyzes carried out led us to conclude that, although Assistive Technology considerably increases the blind people's access possibilities to the EAD scenario, this in itself does not guarantee full access to all the functionalities available from the Virtual Environments of Teaching and Learning. Therefore, in order for distance learning courses to be effectively accessible to the public in question, it is necessary for them to be carefully planned by the instructional team so that blind individuals are respected in their realities and needs.
Keywords: Educação a distância; Inclusão; Pessoa cega; Tecnologia assistiva; Design instrucional; Distance Education; Inclusion; Blind Person; Assistive Technology; Instructional Design; CIENCIAS HUMANAS::EDUCACAO